2022
DOI: 10.1021/acs.energyfuels.2c01533
|View full text |Cite
|
Sign up to set email alerts
|

Minireview of Hydrate-Based CO2 Separation from a CO2/CH4 Gas Mixture: Progress and Outlook

Abstract: Hydrate-based gas separation is a promising method for CO2 capture from CO2/CH4 gas mixtures, and with improved gas separation efficiency, rate of hydrate formation, and gas uptake, this process has the potential to be taken from the lab scale to industry. In this regard, a significant body of work has been conducted in recent years with the aim to enhance the kinetics of the hydrate-based CO2 capture process. The present study presents a review of the kinetic studies performed on the enhancement of hydrate-ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 137 publications
0
4
0
Order By: Relevance
“…This approach is developed based on the solvation ability of CO 2 by water (hydration) in a mixture gas under high pressure. 66 In this regard, amine-containing molecules, as promoters, enhance the capture ability (Figure 2c). This is a low-cost and environmentally friendly CO 2 separation technique, but it has not been developed like other methods.…”
Section: Hydrate-basedmentioning
confidence: 99%
See 1 more Smart Citation
“…This approach is developed based on the solvation ability of CO 2 by water (hydration) in a mixture gas under high pressure. 66 In this regard, amine-containing molecules, as promoters, enhance the capture ability (Figure 2c). This is a low-cost and environmentally friendly CO 2 separation technique, but it has not been developed like other methods.…”
Section: Hydrate-basedmentioning
confidence: 99%
“…This approach is developed based on the solvation ability of CO 2 by water (hydration) in a mixture gas under high pressure . In this regard, amine-containing molecules, as promoters, enhance the capture ability (Figure c).…”
Section: Co2 Capture and Separationmentioning
confidence: 99%
“…The effects of single-component additives (THF, quaternary ammonium salts, CP, SDS, etc.) on the CO 2 capture and separation efficiency have been extensively studied. For compound additives, on the other hand, less current research is available and is still mainly concentrated on the combination of THAs. ,, Therefore, future research should focus closely on the effects of the combination of compound additives, such as thermodynamic additives, surfactants, and nanoparticles, on the CO 2 separation efficiency.…”
Section: Challenges Gaps and Perspectivesmentioning
confidence: 99%
“…Gas hydrates could be used as a molecular sieve, whereby depending upon the shape and size of the hydrate-forming guests, one of the gases from a gas mixture may preferentially occupy the solid hydrate cages and become separated from its mixture . A mini review by Wu et al summarized the state-of-the art research work performed for hydrate-based gas separation for CO 2 capture from CO 2 /CH 4 gas mixtures. A bench-scale dual-bed cyclic gas hydrate process (DB-CGHP) for separation of gas mixtures was presented, and potential for industrial scale-up similar to a pressure swing adsorption process was demonstrated .…”
Section: Applicationsmentioning
confidence: 99%